2014
DOI: 10.1172/jci72723
|View full text |Cite|
|
Sign up to set email alerts
|

ALS-associated mutation FUS-R521C causes DNA damage and RNA splicing defects

Abstract: Autosomal dominant mutations of the RNA/DNA binding protein FUS are linked to familial amyotrophic lateral sclerosis (FALS); however, it is not clear how FUS mutations cause neurodegeneration. Using transgenic mice expressing a common FALS-associated FUS mutation (FUS-R521C mice), we found that mutant FUS proteins formed a stable complex with WT FUS proteins and interfered with the normal interactions between FUS and histone deacetylase 1 (HDAC1). Consequently, FUS-R521C mice exhibited evidence of DNA damage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
244
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(270 citation statements)
references
References 64 publications
19
244
0
3
Order By: Relevance
“…5). These data are consistent with transgenic mice harboring the R521C mutation under control of the Syrian hamster prion promoter (43). However, Qiu et al (43) reported only transgenic mice for FUS mutant R521C, without comparable wild-type transgenic animals.…”
Section: Differences and Commonalities In Fus Overexpression And Misssupporting
confidence: 79%
“…5). These data are consistent with transgenic mice harboring the R521C mutation under control of the Syrian hamster prion promoter (43). However, Qiu et al (43) reported only transgenic mice for FUS mutant R521C, without comparable wild-type transgenic animals.…”
Section: Differences and Commonalities In Fus Overexpression And Misssupporting
confidence: 79%
“…Leading theories propose that ALS mutations cause pathological changes in gene expression/RNA processing Qiu et al 2014). However, whether this reflects reduced function of the mutated proteins, a toxic gain of function, or both is not known (Mackenzie and Neumann 2012).…”
mentioning
confidence: 99%
“…Among the differentially regulated splicing events observed in mutant TDP43 transgenic mice were those involving neurexins 1 and 3, and GluA2-transcripts that are either direct targets of TDP43 or are processed by gene products that are regulated by TDP43 (i.e., ADAR) [14,36]. In contrast to results from mutant TDP43 transgenic mice, overexpression of mutant FUS in an animal model of ALS resulted in the retention of >1000 introns, significantly more than with WT FUS overexpression (177 introns) [63]. In addition, mutant FUS dramatically altered the splicing and expression of an essential neuroprotective agent, brainderived neurotrophic factor (BDNF).…”
Section: Rna Splicingmentioning
confidence: 83%
“…In addition, mutant FUS dramatically altered the splicing and expression of an essential neuroprotective agent, brainderived neurotrophic factor (BDNF). Exogenous replacement of BDNF rescued dendritic and synaptic abnormalities in mutant FUS-overexpressing primary neurons [63], suggesting that abnormalities in RNA processing can be overcome and neuronal function improved in some instances by manipulating downstream signaling pathways.…”
Section: Rna Splicingmentioning
confidence: 97%
See 1 more Smart Citation